Pancreatic beta-cell specific BAG3 knockout results in chronic hyperinsulinemia inducing insulin resistance - Verena Damiani; Alessia Lamolinara; Ilaria Cicalini; Maria Concetta Cufaro; Francesco Del Pizzo; Federica Di Marco; Piero Del Boccio; Beatrice Dufrusine; Michael Hahne; Rossano Lattanzio; Damiana Pieragostino; Manuela Iezzi; et al. (Elsevier, 2023)
Background: Insulin, secreted from pancreatic islets of Langerhans, is of critical importance in regulating glucose homeostasis. Defective insulin secretion and/or the inability of tissues to respond to insulin results in insulin resistance and to several metabolic and organ alterations. We have previously demonstrated that BAG3 regulates insulin secretion. Herein we explored the consequences of beta-cells specific BAG3 deficiency in an animal model. Methods: We generated a beta-cells specific BAG3 knockout mouse model. Glucose and insulin tolerance tests, proteomics, metabolomics, and immunohistochemical analysis were used to investigate the role of BAG3 in regulating insulin secretion and the effects of chronic exposure to excessive insulin release in vivo. Results: Beta-cells specific BAG3 knockout results in primary hyperinsulinism due to excessive insulin exocytosis finally leading to insulin resistance. We demonstrate that resistance is mainly muscle-dependent while the liver remains insulin sensitive. The chronically altered metabolic condition leads in time to histopathological alterations in different organs. We observe elevated glycogen and lipid accumulation in the liver reminiscent of non-alcoholic fatty liver disease as well as mesangial matrix expansion and thickening of the glomerular basement membrane, resembling the histology of chronic kidney disease. Conclusion: Altogether, this study shows that BAG3 plays a role in insulin secretion and provides a model for the study of hyperinsulinemia and insulin resistance.